P12.08 Sti management is hiv prevention: improving access to a comprehensive package of stigma-free srh and hiv services for key populations by implementing the latest who guidelines. (13th September 2015) - McCartney, D; El Hajj, T; Bakomeza, D; Jagdish, N; Maloti, D; Tena, A; Sokolowski, S
Abstract : Introduction: "Shadows and Light" is a three-year project implemented by four IPPF Member Associations and funded by the German BACKUP Initiative. The project developed service capacity that addressed the linked sexual and reproductive health (SRH) and HIV needs of four key populations: transgender people (India); sex workers (Uganda); people who use drugs (Kenya); and men who have sex with men (Cameroon). Often at increased risk of STIs, screening, diagnosis and treatment of STIs are crucial parts of a comprehensive response to HIV. Methods: The initial activities focused on preparing clinic sites, including training of service providers to provide stigma-free services. This involved consultations with key population networks and peer educators to inform development of a full continuum of HIV services, including other STIs, as part of SRH services. Recommended interventions were guided by available WHO guidelines for key populations, and included an assessment of implementation in line with current recommendations. Results: The project contributed to the development of stigma-free SRH services that offered safe access for key populations in each clinic site. The assessment of available STI services found that while syndromic management for all key populations was available, there was limited availability of targeted screening for asymptomatic STIs. While serological testing for syphilis infection was available in some sites, none were screening for gonorrhoeal or chlamydial infections. No periodic presumptive treatment for asymptomatic STIs was undertaken. Conclusion: The inclusion of SRH-related recommendations in the WHO consolidated HIV guidelines for key populations were a critical advancement. By creating a strong link that STI management is HIV prevention enables a greater possibility of addressing within programmes funded by the Global Fund to fight AIDS, Tuberculosis and Malaria. However, additional implementation tools are required to support strengthening of STI-specific services for key populations. Disclosure of interest statement: Nothing to declare.